2006
DOI: 10.1111/j.1365-2958.2006.05027.x
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal relBE2 toxin–antitoxin locus of Streptococcus pneumoniae: characterization and use of a bioluminescence resonance energy transfer assay to detect toxin–antitoxin interaction

Abstract: SummaryProteic toxin-antitoxin (TA) loci were first identified in bacterial plasmids, and they were regarded as involved in stable plasmid maintenance by a socalled 'addiction' mechanism. Later, chromosomally encoded TA loci were identified and their function ascribed to survival mechanisms when bacteria were subjected to stress. In the search for chromosomally encoded TA loci in Gram-positive bacteria, we identified various in the pathogen Streptococcus pneumoniae . Two of these cassettes, sharing homology wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 63 publications
5
74
0
Order By: Relevance
“…The number of TAS reported to exist in S. pneumoniae was relatively small, with at most five in strain R6 and six in virulent strain TIGR4, when they were first reported in 2005 to 2006 (117,122). About 4 years later, the number was increased to up to eight TAS in the genome of S. pneumoniae (118).…”
Section: Tas In S Pneumoniae: So Fewmentioning
confidence: 96%
See 2 more Smart Citations
“…The number of TAS reported to exist in S. pneumoniae was relatively small, with at most five in strain R6 and six in virulent strain TIGR4, when they were first reported in 2005 to 2006 (117,122). About 4 years later, the number was increased to up to eight TAS in the genome of S. pneumoniae (118).…”
Section: Tas In S Pneumoniae: So Fewmentioning
confidence: 96%
“…Even though TAS of G ϩ bacteria are also widely distributed and have been found in both chromosomes and plasmids, they are comparatively less well characterized. For instance, some of the well-studied TA genes of G Ϫ bacteria have also been discovered in G ϩ bacteria, such as mazEF in S. aureus (40) and relBE and yefMyoeB in S. pneumoniae (117). Nevertheless, there are cases in which specific TAS seem to play different roles in G ϩ and in G Ϫ bacteria: the epsilon-zeta TA cassette stabilizes plasmids in E. coli less efficiently than in Bacillus subtilis.…”
Section: Bacterial Tas: What Are They Really For?mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of TA loci varies from none (as in the case of many obligate host-associated bacteria) to as many as 45 found in the Nitrosomonas europaea genome (189). The chromosomal TA modules of E. coli have thus far been the most extensively characterized, but note that chromosomal TA modules in other organisms including Streptococcus mutans (150), Bacillus anthracis (1), S. aureus (66), and S. pneumoniae (123,178) have recently been studied. Several reviews detailing the advances in chromosomal TA module research have been published (33,(57)(58)(59)(60)80); therefore, this review will focus on two well-characterized E. coli TA modules, MazEF and RelBE, as well as on the E. coli TA-like module HipBA, highlighting the evidence for and evidence against their controversial roles in eliciting bacterial cell death.…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…Therefore, at present, the RelE-RelB TA system is considered to be a stress-response element rather than a cell-killing module [102]. However, it was shown that in the case of the homologous pneumococcal RelBE2 system, prolonged exposure of the cells to the toxin resulted in the inability to rescue the cultivability of the cells by subsequent expression of the antitoxin [104].…”
Section: The Rele-relb System As Stress-response Elementmentioning
confidence: 99%